Break the superheat temperature limitation of induction skull melting technology. (5th February 2023) - Zhang, Chaojun; Cao, Fuyang; Zhang, Lunyong; Jin, Zhishuai; Cao, Guanyu; Qiu, Ziao; Shen, Hongxian; Huang, Yongjiang; Jiang, Sida; Sun, Jianfei
Graphical abstract: Highlights: A full coupling model for induction skull melting technology was proposed. The limitation mechanism of melt superheat temperature was investigated. Reducing heat loss is the key to raising superheat temperature. Proposed methods for increasing the superheat temperature of the melt. Abstract: Overcoming the limitation of low superheat temperature problem is key for the applications of the induction skull melting technology in many important high melt point metals used in fields such as aerospace. The present paper presents an advanced numerical study to explain the mechanism of melt superheat temperature. A coupling model between electromagnetic, thermal, phase and fluid flow fields was established, which accurately predict the temperature and meniscus shape in the research domain. The simulation results show that the forced convective heat transfer caused by electromagnetic force in the melt and the current passing through phenomenon between molten melt and crucible were the key to influence the superheat temperature and electrical efficiency. Furthermore, it was discovered that convection suppression in the melt by employing an external DC coil and increasing the thermal resistance between the skull and the crucible could increase the melt superheat temperature effectively. Increasing the thermal resistance between the skull and the crucible also leads to an increase in the superheat temperature, which could be achieved by enhancing the interface roughness. The present work would shed lights on the design of new generation induction crucible to obtain high superheat temperature melt.